COMPLEMENTING THEORY WITH PRACTICE TO ENHANCE STUDENTS’ LEARNING - Suliman, Muhammad Imran; Imran, Faiqa; -ur-Rahim, Ikram; Shafiq, Anser; Qayum, Iftikhar (Journal of Ayub Medical College Abbottabad, 2016)
Background: Combining cognitive skills teaching related to the techniques leads to better understanding in a skill training course; but still there a substantial disagreement in curriculum on such combinations. This study aims to help guide the designers in making the outline of instructional plan for a Clinical Skills Module (CSM) for the undergraduates. Objectives were to assess performance of students on a clinical skill after training by two different models of (hands-on only or with cognitive skills) instructions and explore their perception on the employment of educational strategies through Focus Group Discussions (FGD) through a Sequential mixed method study design: (1) Quantitative (Pre- and post-assessments and comparing their results (2) Qualitative (Exploration of perspectives through constructivist approach using qualitative phenomenological design) The study was conducted during the month of September, 2015 at Rabigh Medical College, King Abdul Aziz University, Jeddah. Methods: Students entering fourth year were randomized to two groups to participate in pre-post OSCE using global rating scale and their scores were compared. The examiners were kept blinded to the randomization of students undergoing two separate training methods. The test group (group A) was trained for both procedural as well as cognitive skills whereas the control group (Group-B) was trained only with hands-on practice. Later their perception about the addition of cognitive skills to improve of procedural skills was explored through focus group discussions. The recorded audio tapes of FGDs were transcribed and analysed thematically. Triangulation of themes and trends was achieved by relating the content analysis to the relevant frequency of quotes. Auditing of the data verification was done by all the authors separately. Results: A total of 42 students completed both pre- and post-tests. As a result, student performance in OSCE significantly increased from pre- to post-test (p<0.001) in both the groups; on the other hand no statistically significant difference was found in the pre- and post- test scores between groups A and B (p=0.108). Five themes (1) advantages, (2) disadvantages of combining theory with practice, (3) time balance in teaching a skill, (4) training on skills, (5) skills-assessment, were found prevalent on thematic analysis of the FGDs. Conclusion: Students’ ability to grasp the procedural skills was not significantly different when they acquire the cognitive skills in addition to the practical sessions. Students were more convinced to adopt combination of the two in the learning of procedural skills. Keywords: Objective structured clinical examination, assessment, student learning, cognitive skills, skill centre